Numerical Simulation to Evaluate air Pollutants Resulting from Fuel Combustion in a Thermal Power Plant under Different Conditions - Rafid M. Hannun, Ali H. Abdul Razzaq (Mathematical Statistician and Engineering Applications, 2022)
Predicting the release of pollutant concentrations into the atmosphere is an essential element in assessing potential environmental damage from industrial emissions. This paper presents a numerical study to model the dispersion of pollutants from the stacks of the thermal power plant in Nassiriya, Iraq. The power plant operates on two types of fossil fuels (crude oil and natural gas) and emits pollutants in the form of (CO, CO2, SO2, and NOX). A 3D mathematical model based on fluid mechanics equations is used in conjunction with a modified standard k-? turbulence model to calculate flow and scattering at the atmospheric microscale (for distances of several kilometers). In order to confirm the current study’s validity, the created numerical model was compared with the previous experimental and theoretical models, and the comparison results showed good agreement. These equations were solved using the ANSYS FLUENT (CFD) 2020 R2 program to show the results of flowing smoke columns at variable factors of wind speed, pollutant columns, stack heights, and wind direction angles.